2003
DOI: 10.1161/01.str.0000091393.32060.0e
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Measures of Atherosclerosis and Risk of Stroke

Abstract: Background and Purpose-Several measures of atherosclerosis predict the risk of stroke. However, a comparison between various measures of atherosclerosis is lacking, and limited information exists on the added value of individual measures of atherosclerosis to cardiovascular risk factors. We compared different measures of atherosclerosis in relation to stroke. Methods-The study was based on the prospective cohort of the Rotterdam Study and included 6913 participants who did not suffer from previous stroke. At b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
192
2
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(210 citation statements)
references
References 14 publications
8
192
2
8
Order By: Relevance
“…1 The prevalence of the renal artery stenosis in the present study was 3%, This is the first time to our knowledge that this prevalence has been reported in a free-living population sample. In a previous autopsy study, this figure ranged from 4.3% to 12%.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…1 The prevalence of the renal artery stenosis in the present study was 3%, This is the first time to our knowledge that this prevalence has been reported in a free-living population sample. In a previous autopsy study, this figure ranged from 4.3% to 12%.…”
Section: Discussionsupporting
confidence: 55%
“…1 Magnetic resonance angiography (MRA) has advantages over conventional angiography in that it lacks ionizing radiation, there are no risks otherwise associated with arterial cannulation, and there is less nephrotoxicity than with iodinated contrast agents on the account of the smaller volumes of contrast agents administered in MRA. Recently the concept of imaging of the whole arterial system, except the coronary arteries, with one intravenous injection of gadolinium contrast and a moving table, ie, whole-body magnetic resonance angiography (WBMRA), 2 has been introduced.…”
mentioning
confidence: 99%
“…(16)(17)(18)(19)(20)(21) Recently, we and others have reported that AAC can be measured on vertebral morphometric images obtained by dual-energy X-ray absorptiometry (DXA) and that the presence of AAC independently predicted incident MI, stroke, and cardiovascular events, even after adjusting for traditional cardiovascular risk factors. (22)(23)(24)(25) AAC also has been inversely associated with BMD in many studies.…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive imaging of the carotid arteries has been suggested to be a valid "window" or indicator site for general atherosclerosis in epidemiological studies (17,18Salonen 1993 (20), the relation between IMT and stroke was independent of plaque. Taken together, these data provide supportive evidence for the use of IMT measurements as a marker of generalized atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%